Democratic Republic of the Congo : Request for a Three-Year Arrangement under the Poverty Reduction and Growth Facility and for the First Annual Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper examines the Democratic Republic of the Congo's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and for the First Annual Program. The authorities requested a three-year PRGF arrangement in support of their program covering April 1, 2002-July 31, 2005, in an amount equivalent to SDR 580 million. The authorities have also steadfastly implemented a Staff-Monitored Program covering June 2001-March 2002, aiming principally at stabilizing the economic situation, and laying the foundation for the restoration of growth and reconstruction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet